Fabrication and characterization of AlGaAs/GaAs pseudomorphic high electron mobility transistors for power applications - Tan, Chee Leong (2008)
A robust process technology using optical and electron beam lithography has been developed for 0.25 µm gate length AlGaAs/GaAs pseudomorphic high electron mobility transistors (PHEMTs). These devices, for power applications at microwave frequencies, demonstrated a high gate-drain breakdown voltage and a high drain current. In-depth studies have been conducted to investigate issues related to the surface trapping and hot carrier induced degradation in BCB-passivated devices. The drain current transient technique reveals that BCB reduces the density of surface states compared to unpassivated PHEMTs. Hot carrier stress tests indicate that dc degradation under high gate-drain field is due to trapping of hot electrons in states within the BCB and/or at the interface between the semiconductor and the BCB in the gate-drain access region. For the SiN-passivated devices, it is due to the trapping of holes in the AlGaAs Schottky layer underneath the gate and in the thin oxide interface layer between the gate metal and the AlGaAs surface. The PHEMT technology developed was also extended to the design and fabrication of C-X-Ku broadband and Ku-band power amplifier MMICs.